2005
DOI: 10.1073/pnas.0509585102
|View full text |Cite
|
Sign up to set email alerts
|

Placing confidence limits on the molecular age of the human–chimpanzee divergence

Abstract: Molecular clocks have been used to date the divergence of humans and chimpanzees for nearly four decades. Nonetheless, this date and its confidence interval remain to be firmly established. In an effort to generate a genomic view of the human-chimpanzee divergence, we have analyzed 167 nuclear protein-coding genes and built a reliable confidence interval around the calculated time by applying a multifactor bootstrap-resampling approach. Bayesian and maximum likelihood analyses of neutral DNA substitutions show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
103
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(115 citation statements)
references
References 51 publications
(66 reference statements)
10
103
1
1
Order By: Relevance
“…Our molecular dating estimates are generally in agreement with a large number of studies using different calibration points; Kumar et al [26], Glazko and Nei [27], and even the classical study of Sarich and Wilson [28] found a molecular divergence of HC at 5-7 Myr, 6 Myr, and 5 Myr, respectively. Speciation, defined as the total cessation of gene flow, is necessarily more recent than these molecular dates, and our value of approximately 4 Myr agrees very well with the time suggested by Patterson et al [2] for complete cessation of gene flow.…”
Section: Discussionsupporting
confidence: 90%
“…Our molecular dating estimates are generally in agreement with a large number of studies using different calibration points; Kumar et al [26], Glazko and Nei [27], and even the classical study of Sarich and Wilson [28] found a molecular divergence of HC at 5-7 Myr, 6 Myr, and 5 Myr, respectively. Speciation, defined as the total cessation of gene flow, is necessarily more recent than these molecular dates, and our value of approximately 4 Myr agrees very well with the time suggested by Patterson et al [2] for complete cessation of gene flow.…”
Section: Discussionsupporting
confidence: 90%
“…These divergence times are broadly consistent with other estimates (Adkins et al 2003;Douzery et al 2003;Steppan et al 2004). Divergence times for human, chimpanzee, and macaque were taken from other studies (Nei and Glazko 2002;Kumar et al 2005;Patterson et al 2006), as both chimpanzee and macaque were not included in the Springer et al study. Reanalysis of the data using the most extreme value for mouse-rat divergence in the literature (33 MY) (Nei and Glazko 2002) or increasing the human-chimpanzee split to 10 MY does not qualitatively affect our conclusions (supplemental Table 2 at http:/ /www.genetics.org/supplemental/).…”
Section: Data Collectionsupporting
confidence: 77%
“…Given previously estimated divergence times of these species (∼266 and ∼6 MYs for frog and primate, respectively; ref. 17), frogs still appear to have a much slower substitution rate (0.749 × 10 −9 versus 3.12 × 10 −9 substitutions per site per year). Thus, among tetrapods, the genomes of ectotherms appear to evolve more slowly than do those of endotherms.…”
Section: Resultsmentioning
confidence: 96%